GAMBARAN PENGETAHUAN PASIEN TUBERKULOSIS PARU DALAM TERAPI DIET TKTP DI RUANG RAWAT INAP RUMAH SAKIT SANTA ELISABETH MEDAN. - Herianto Silvester Sitanggang; Magda Siringoringo (STIKes Santa Elisabeth Medan, 2017)
Pulmonary Tuberculosis is a contagious disease directly caused by TB germs. The main symptoms are sputum mixed with blood, decreased appetite, and decreased BB. BB decrease can reach 10%. Condition of TB patient can be recovered by consuming nutritious food. The importance of attention to food intended for people with infectious diseases, especially Pulmonary TB patients include the availability of energy substances, proteins, fats and carbohydrates provided by the hospital. Goal: : To describe the knowledge of lung tuberculosis patients in TKTP diet therapy In the inpatient room of Santa Elisabeth medan hospital. Methods: This case study method is a descriptive type. Result: The results of this study indicate the knowledge of pulmonary TB patients about TKTP diet is good as much as 80% and enough as much as 20%. So knowledge of lung TB patients at Santa Elisabeth Hospital Medan is good. Conclusion: For nurse to help information about TKTP diet in Lung TB patient.